Discord in Matrilineality: Insight into the Khasi Society in Meghalaya. (July 2018) - Roy, Animesh
Abstract: The matrilineal society of the Khasi tribe in Meghalaya is now undergoing a transitional phase, whereby, on the one hand, the government is attempting to destine its traditional political institutions into more efficient instruments of democratic decentralisation, resulting into contradictions over the 'manoeuver of village-level governance' between the government and the Khasi Hills Autonomous District Council (KHADC), and, on the other hand, a section of Khasi men presuming themselves to be deprived of the property rights wanting to be recognised at par with the Khasi women. Given such a situation, this piece of work attempts to analyse the status of both Khasi males and females in terms of their involvement in social, economic and political affairs under matrilineality. It also critically evaluates the fecundity of the Village Administration Bill (VAB) of 2014 keeping a gender perspective in focus. The article, however, argues that despite having claimed to have placed women in higher position than men in the society, the Khasi matrilineality vitriolically relegates the role of women in politics and governance, thus portraying a contradiction. This contradiction even vividly exists in the recent VAB passed by the KHADC. Our primary survey also reflects that the female workforce has mostly established a foothold in the low-profile economic activities while dominance of the male workforce is found in those economic activities that are associated with a higher social status.